1986
DOI: 10.1111/j.1399-6576.1986.tb02397.x
|View full text |Cite
|
Sign up to set email alerts
|

Per‐ and postoperative changes in coagulation and fibrinolytic variables during abdominal hysterectomy under epidural or general anaesthesia

Abstract: Blood coagulation and fibrinolysis were studied in 20 premenopausal women undergoing abdominal hysterectomy under general anaesthesia (GA) or high epidural analgesia (EDA). As expected, the adrenocortical stress response was suppressed in the EDA group. The Factor VIII complex (F VIII:C, F VIII R:Ag = von Willebrand factor), known to be related to adrenocortical activity and/or vessel wall reactivity, was found to increase less in the EDA group. With regard to all the other variables analysed there were no sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 24 publications
2
17
1
1
Order By: Relevance
“…Ten studies were excluded because they were quasi-randomised,8-17 and six were excluded because not all participants were randomised and separate information on the randomised patients was not available 18-23. One trial was excluded because the groups differed with respect to heparin treatment as well as anaesthetic technique 24.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies were excluded because they were quasi-randomised,8-17 and six were excluded because not all participants were randomised and separate information on the randomised patients was not available 18-23. One trial was excluded because the groups differed with respect to heparin treatment as well as anaesthetic technique 24.…”
Section: Resultsmentioning
confidence: 99%
“…Epidural analgesia (EDA) lowers the incidence of postoperative thrombosis (Modig et al 1981) and attenuates the Factor VIII-complex response to surgical stress (Modig et al 1983, Bredbacka et al 1986). …”
Section: Discussionmentioning
confidence: 99%
“…Venous blood samples were collected by direct venipuncture of a cubital vein using a sharp 1.4 mm needle and without stasis on the forearm, as earlier described (Bredbacka et al 1986). The samples were collected on the day before surgery (Day -I), during surgery, i.e., 10 minutes after insertion of the femoral component (Day 0), the first (Day 1).…”
Section: Methodsmentioning
confidence: 99%
“…It has also been shown that local anesthetics activate the fibrinolytic system, reduce factor VIII, plasminogen and alfa-2-antiplasmin concentration, and inhibit platelet aggregation [9,10]. We therefore designed a study to determine whether the application of local anesthetics to the intraperitoneal space following surgery might be able to prevent intraabdominal adhesions.…”
Section: Introductionmentioning
confidence: 99%